Toksisitas Limbah Pabrik Minyak Kelapa Sawit Terhadap Benih Ikan Nila Merah (Oreochromis sp.) - Syafriadiman, Syafriadiman (Fakultas Perikanan dan Kelautan Universitas Riau, 2016)
Research of toxicity of industrial palm oil wastewater and sub lethal test to Oreochromis sp. has been conducted on February 1st to March 1st 2009 in Aquaculture Technology Laboratory, Fisheries and Marine Science Faculty University of Riau. Objective of this research is to determine the concentration of a test material or the level of an agent that produces a deleterious effect on Oreochromis sp. during a short-time exposure under controlled condition. In this study, static 96-h acute toxicity tests were carried out using Oreochromis sp. as test organisms. Probit analysis using the computer software EPA and graphical method were used to caculate the 96-h LC50 depending on data suitability. Results of the 96-h LC50 and Biological Savety Level of the industrial palm oil waste water were 126,06 ml/l and 1.26 ml/l respectively.